PEMODELAN SPASIAL UNTUK KAJIAN EFEKTIVITAS JANGKAUAN PELAYANAN PASAR TRADISIONAL MENGGUNAKAN CITRA QUICKBIRD (Kasus : Kecamatan Banguntapan dan Piyungan) - , ASRI LARASATI .P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research has purposes to know the accuracy of Quickbird imagery as a data source which uses to extract some information about settlement and pre means of traditional markets, to do spatial modeling especially network analysis to determine the range of the traditional markets service, and to determine the effectiveness of the range of traditional markets service in the District Banguntapan and Piyungan. Quickbird satellite imagery and field surveys are used as the primary data sources. The methods which are used to determine the range of the traditional markets service are scorring, overlay, and network analysis. In this research, a variable rate residential density, regularity settlements, settlements distance to the center of activities, and the level of disadvantaged populations are used as pharameters to decide the range of the traditional markets service. GIS is used to obtain the value of the potential demand through the overlay method with dignity. In this result, the value of accuracy test for land use Quickbird imagery interpretation is 92.54%, and residential density is 88%, while the settlements regularity is 89%. The range of Ngipikâs market service is 12.45 km2 or 35.55%, the range of Panasanâs market service is 13.88 km2 or 39.63%. Totally, the range of Panasanâs market and Ngipikâs market service is 26.33 km2 or 75.69% of the total area district Piyungan and Banguntapan. The highest effectiveness percentage is 2.21 km2 or 52.74% from the broad range of traditional markes service to potential consumers which is located in Sitimulyo. The range of traditional markets service in District Banguntapan and Piyungan has less effective toward to potential customers distribution. The highest percentage of the traditional markets service which are categorized âless effectiveâ is 0.8 km2 which is located in Tamanan and about 0.23 km2 or 100% from the entire range of traditional markets service to the potential customers in the District Banguntapan and Piyungan which is located in Jagalan.